Synthesis of low-molecular weight fucoidan derivatives and their binding abilities to SARS-CoV-2 spike proteins. Issue 12 (15th September 2021) - Koike, Tatsuki; Sugimoto, Aoi; Kosono, Shuhei; Komaba, Sumika; Kanno, Yuko; Kitamura, Takashi; Anzai, Itsuki; Watanabe, Tokiko; Takahashi, Daisuke; Toshima, Kazunobu
Abstract : Synthesized fucoidan derivative 10 exhibited inhibitory activities against the binding of heparin with several SARS-Cov-2 spike proteins, but did not inhibit factor Xa activity that could otherwise lead to undesirable anticoagulant activity. Abstract : Fucoidan derivatives 10–13, whose basic sugar chains are composed of repeating α(1, 4)-linked l -fucopyranosyl residues with different sulfation patterns, were designed and systematically synthesized. A structure–activity relationship (SAR) study examined competitive inhibition by thirteen fucoidan derivatives against heparin binding to the SARS-CoV-2 spike (S) protein. The results showed for the first time that 10 exhibited the highest inhibitory activity of the fucoidan derivatives used. The inhibitory activity of 10 was much higher than that of fondaparinux, the reported ligand of SARS-CoV-2 S protein. Furthermore, 10 exhibited inhibitory activities against the binding of heparin with several mutant SARS-CoV-2 S proteins, but was found to not inhibit factor Xa (FXa) activity that could otherwise lead to undesirable anticoagulant activity.